RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA PEGAWAI MENGGUNAKAN MOORA BERBASIS WEBSITE - Dwi Putri Ayu Lestari; Zein Vitadiar, Tanhella; Setyo Permadi, Ginanjar; Kristianto, Hery (Fakultas Teknologi Informasi, 2024)
Employee performance evaluation is a crucial element in human resource management to assessindividual contributions to organizational goals and identify areas where productivity can be improved.Manual assessments that are subjective often lack accuracy and fairness. This research aims to design aweb-based decision support system for employee performance evaluation using the MOORA method(Multi-Objective Optimization on the basis of Ratio Analysis) for the Jombang District Education andCulture Office. MOORA was chosen for its effectiveness in handling multi-criteria in complex decisions.The system facilitates access and use with web technology. Requirements study, design, implementation,and testing have shown that the system provides more objective and accurate evaluations compared tomanual methods. This system is expected to improve the quality of performance evaluations and supportdata-driven decision-making at the Jombang District Education and Culture Office, serving as a model forother institutions in enhancing accuracy and precision in evaluating employee performance. The rankingresults recommend employee rank 1, Hadi Suwito, A.md, with a final score of 0.0217, employee rank 2,Weni Siswin Agustin, S.sos, with an accumulated score of 0.0183, and employee rank 3, Diyanto, with anaccumulated score of 0.0127.Keywords: DSS, Moora, Employee Appraisal, Performance, Education and Culture Office of JombangDistrict